Business Models for Industry 4.0: A Book Review - Alfian Rosiadi (Pusbindiklatren Bappenas, 2024)
The book entitled “Business Models for Industry 4.0: Concepts and Challenges in SME Organizations” discusses the challenges and opportunities faced by small and medium enterprises (SMEs) in the Industry 4.0 era. The author explores concepts such as Economy 4.0, Society 5.0, sustainable consumption, digital technology integration, and the need for customer engagement. Based on this background, the author emphasizes the importance of new business models, interdisciplinary knowledge, and continuous learning in the context of Industry 4.0 to develop value from SMEs.